The Efficiency Test of Additional Multi Protocol Label Switching Network Protocol Over Open Shortest Path First Network Using Graphic Network Simulator 3 - Ghandie Kurnia Widi; Muhammad Luthfi Baihaqi; Ari Sriyanto Nugroho; Sidiq Syamsul Hidayat (Institute of Advanced Engineering and Science, 2015)
Technological developments in the field of fiber optic telecommunications with the media of the backbone network is faster in comparison with other technologies. In the process, the telecommunications industry use the metro ethernet configuration with Multi Protocol Label Switching (MPLS) network and Open Shortest Path First (OSPF) as the backbone network. This study aims to answer the question of how much the effect of adding the MPLS network protocol on OSPF network. So from this research can be known the value of the efficiency of the addition MPLS network protocol on OSPF network based on network performance using a software simulator GNS3 as its backbone through a step-test. From the test results concluded that based on the delay by the load, MPLS makes network performance more efficient by 67.04%, based on the packet loss and link failure conditions, MPLS makes network performance more efficient by 1.1%, but based on the no-load delay, OSPF has more efficient network performance by 41.96%, and based on the transfer rate, OSPF has a more efficient network performance by 5.2%, to delay normal conditions both have a performance with an average value of 0% packet loss. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.7600